Internal contradictions of nature reserve business - Olexandra Svitlychna (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії)
Protected areas perform such functions as protective, scientific, aesthetic and recreational. The most important of them are recreational and environmental and their interests conflict with each other. In the early XX century in the world there were two areas of the environmental movement: environmental protection and conservation of natural resources. Protection of cultural values in Europe complicated of structure protected areas and changed their development toward recreational using. At that time the development of the Ecology has led to prevalence of ideas that protected areas must perform only ecological functions.